Simplified approach to the shakedown problem of I-cross-sections under two-directional bending = Uproszczona metoda rozwiązania problemu przystosowania przekrojów dwuteowych na zginanie dwukierunkowe - Aliawdin, Piotr; Bryś, Gerard (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The report presents an analytical model suitable to carry out a shakedown and limit analysis of steel thin-walled beam cross-sections under low-cyclic loadings. The loads and actions are quasi-static, any dynamic effects and fatigue failure are not considered. Initial stresses (due to prestressing) as well as residual stresses are allowed. The vector of variable repeated forces contains the axial force, the bending moments about two principal axes of cross-section and warping moment. Shear forces, moments of pure torsion and bending torsion are also taken into account but their influences are assumed to be minor. Prestressing forces and thermal actions are considered herein as one of the load types with zero vector of resultant internal forces. Cross-sections of beams may have any geometrical form, but analysis are performed for the I-type beam under bending about two principal axes, without warping moment. The numerical results for cyclic load are compared with the analogous data for one-path load on the cross-sections.
Keywords: belka; przekrój poprzeczny; zginanie dwukierunkowe; steel thin-walled beams; shakedown